Islam Indonesia: Diskursus Islam Kultural dan Islam Politik - Muhammad Firdaus (JURNAL INDO-ISLAMIKA, 2019)
This study discusses two faces of Islam regarding its relationship with the state, namely cultural Islam and political Islam. Cultual Islam believes that to spread Islamic values does not have to take power, but can also pay attention to the grassroots, by preaching to the community, establishing educational, health and economic institutions. Whereas cultural Islam is more power-oriented, they believe that with that power it can be easy to apply Islamic teachings, and some even want to change the shape of the country into an Islamic state. Some political Islamists participate in parties, and some are non-parties. Usually, those who are non-party are more likely to be radical. Both have advantages and disadvantages, what is clear is that cultural Islam is more humane and has an impression on society.